2014
DOI: 10.1111/nan.12160
|View full text |Cite
|
Sign up to set email alerts
|

Memory deficits correlate with tau and spine pathology in P301S MAPT transgenic mice

Abstract: In P301S mice, memory deficits precede the onset of locomotor dysfunction and coincide with the appearance of conformationally changed, S202-phosphorylated tau and reduced spine density in the absence of neuronal cell loss in the hippocampus. Our finding provides insights into the toxic effects of different tau species in vivo and may facilitate the development of new therapies against neurodegenerative tauopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 31 publications
6
53
1
Order By: Relevance
“…Overall, our data lend direct support to the patho-physiological relevance of non-filamentous, oligomeric tau. Nevertheless, strong correlations with cognitive decline were also observed for conformational and phospho-tau as previously reported in humans [25, 30] and animal models [43, 44, 83]. Our data expand on the suggested disruptive role of monomeric phospho-tau [41], and suggest oligomerization caused by pathological modification of monomeric tau to play a key role.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our data lend direct support to the patho-physiological relevance of non-filamentous, oligomeric tau. Nevertheless, strong correlations with cognitive decline were also observed for conformational and phospho-tau as previously reported in humans [25, 30] and animal models [43, 44, 83]. Our data expand on the suggested disruptive role of monomeric phospho-tau [41], and suggest oligomerization caused by pathological modification of monomeric tau to play a key role.…”
Section: Discussionsupporting
confidence: 89%
“…In P301S Tau mice, the fraction of thin spines was found to be strongly reduced, whereas that of mushroom spines was found to be increased compared to controls [16]. Another study reported that, even at an early age, P301S Tau transgenic mice are characterized by a lower average spine density, length, area and volume compared with wild-type mice, concomitant with an impaired learning at this age in the Morris water maze [38]. Together with our findings this reveals that FTD mutant forms of Tau accumulate in the spine, which results in morphological changes and, subsequently, spine loss.…”
Section: Discussionmentioning
confidence: 91%
“…More importantly, compelling evidence indicates that tau pathology is closely associated with the severity of cognitive deficits in patients with AD or FTD (Giannakopoulos et al, 2003;Xu et al, 2014). In view of its critical role in the pathogenesis of these 2 diseases, more needs to be done to elucidate potential mechanisms affecting the formation and progression of tau pathology.…”
Section: Introductionmentioning
confidence: 98%